Management of Facilities and Infrastructure at Sunan Ampel PGRI 2 Kindergarten in Support Children'S Activities - Mirrohmatilla, Mirrohmatilla (Pelangi (e-Journal), 2025)
The ongoing education process for children depends heavily on adequate facilities and infrastructure. Effective facility management creates a safe, comfortable, and enjoyable learning environment, thereby improving the quality of education. In the context of early childhood education, particularly in kindergartens, the availability of play equipment, child-friendly classrooms, and safe play areas is crucial. Sunan Ampel PGRI 2 Kindergarten is committed to providing supporting resources to foster comprehensive child development. The school uses a collaborative approach in managing these facilities, involving school leaders, teachers, the school committee, and parents to ensure that facility planning is responsive to children's developmental needs. However, challenges, including budget constraints and community participation, can hinder ideal management practices. Despite these obstacles, improvements have been seen since 2020 thanks to the active support of the school committee. The presence of essential educational facilities and infrastructure is crucial for creating an effective and interactive learning environment. This study uses a descriptive qualitative approach to examine how facilities and infrastructure are managed at Sunan Ampel PGRI 2 Kindergarten, including direct observation, stakeholder interviews, and documentation analysis. The research findings revealed that the school has developed a well-organized facility system that encourages active learning. Continuous collaboration, regular evaluation, and community involvement are crucial to maintaining and improving these facilities. Effective facility management at Sunan Ampel PGRI 2 Kindergarten plays a crucial role in ensuring a conducive learning environment for optimal child growth and development, demonstrating the importance of school-community partnerships in improving educational quality.